2017
DOI: 10.1186/s12875-017-0628-y
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of depression by primary care clinicians in rural Ethiopia

Abstract: BackgroundDepression is a common health condition affecting up to a third of patients attending primary care, where most of the care for people with depression is provided. Adequate recognition of depression is the critical step in the path to effective care, particularly in low income countries. As part of the Programme for Improving Mental healthcare (PRIME), a project supporting the implementation of integrated mental healthcare in primary care, we evaluated the level of recognition of depression by clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 43 publications
4
77
1
Order By: Relevance
“…Similarly primary care physicians in Chile were able to detect 48% of cases of common mental disorders presenting in primary care [ 34 ]. However, the detection rate found in the current study compares well with detection rates of mental disorders or depression in primary care reported in other LMICs, which range from 0 to 1.3% [ 35 – 37 ]. The low detection rates of depression among PHCWs in LMICs have been attributed to low level of mental health knowledge and skill among PHCWs, and the prioritization of physical conditions over mental disorders when depressed patients present with multiple somatic symptoms [ 35 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly primary care physicians in Chile were able to detect 48% of cases of common mental disorders presenting in primary care [ 34 ]. However, the detection rate found in the current study compares well with detection rates of mental disorders or depression in primary care reported in other LMICs, which range from 0 to 1.3% [ 35 – 37 ]. The low detection rates of depression among PHCWs in LMICs have been attributed to low level of mental health knowledge and skill among PHCWs, and the prioritization of physical conditions over mental disorders when depressed patients present with multiple somatic symptoms [ 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…However, the detection rate found in the current study compares well with detection rates of mental disorders or depression in primary care reported in other LMICs, which range from 0 to 1.3% [ 35 – 37 ]. The low detection rates of depression among PHCWs in LMICs have been attributed to low level of mental health knowledge and skill among PHCWs, and the prioritization of physical conditions over mental disorders when depressed patients present with multiple somatic symptoms [ 35 ]. The low capacity of the sampled facilities to provide quality chronic care for depression and the low detection rates for depression by the PHCWs demonstrate important gaps in both the organisational structures and manpower capacity of the frontline facilities to respond to common perinatal mental health conditions in a fully functional integrated chronic care model.…”
Section: Discussionsupporting
confidence: 82%
“…Only one of the included studies reported on predictors of detection, which noted severity of symptoms and suicidality as significant predictors 28 . Overall, these are consistent findings with what is known about the detection of depression 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in the neighbouring district, the lifetime prevalence of schizophrenia is reported to be 0.5% [ 2 , 14 ]. The prevalence for bipolar disorder is 0.6% for males and 0.3% for females while major depression has 11% prevalence at the healthcare facility level [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%